Let's talk about stuttering - Kent, Susan, 1942- (New York : PowerKids Press, 2000)
Discusses stuttering, the embarrassment it may cause, and the possibility of self-esteem for those with this condition.
Includes index.
13
Keywords: Stuttering -- Juvenile literature; Stuttering